Penggunaan Media Audio Visual untuk Meningkatkan Hasil Belajar Salat Fardu di Madrasah Tsanawiyah Riyadhul Muttaqin As`Adiyah Desa Sungai Tawar, Kecamatan Mendahara, Kabupaten Tanjung Jabung Timur Provinsi Jambi - Sri Rahmi Pitriani Alam; Kartubi Kartubi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the implementation of audiovisual media and the improvement of learning outcomes for obligatory prayers through their application among seventh-grade students at Riyadhul Muttaqin As'adiyah Islamic Junior High School in Sungai Tawar Village, Mendahara District, East Tanjung Jabung Regency, Jambi Province. This study is a Classroom Action Research (CAR) conducted in three cycles: pre-cycle, cycle I, cycle II, and cycle III. The subjects were seventh-grade students participating in Islamic Religious Education lessons on the practical topic of obligatory prayers. The results show that the use of audiovisual media was implemented in a gradual and systematic manner. In cycle I, the media served as a means of introducing basic prayer movements and recitations. In cycle II, learning was developed through interactive approaches such as discussions, group practice, and analysis of correct and incorrect movements. In cycle III, the media served as reinforcement and reflection, while practice was conducted more independently. The use of audiovisual media not only increased students' attention and motivation to learn but also strengthened conceptual understanding and practical skills. Significant improvements in learning outcomes were seen in each cycle. In the pre-cycle, all students were in the Starting to Develop (MB) category. In the first cycle, this improved to Developing as Expected (BSH). In the second cycle, some students reached the Very Well Developing (BSB) category. In the third cycle, all students reached the Very Well Developing (BSB) category with a very high class average. These improvements encompassed cognitive, psychomotor, and affective aspects in learning the Fardhu Prayer. Thus, the use of audio-visual media has proven effective in improving the learning outcomes of Fardhu Prayer in seventh-grade students.